Sequential injection spectrophotometric determination of zinc(II) in pharmaceuticals based on zinc(II)-PAN in non-ionic surfactant medium - Thanasarakhan W. (2014)
A sequential injection analysis (SIA) spectrophotometric method for the determination of trace amounts of zinc(II) with 1-(2-pyridylazo)-2-naphthol (PAN) is described. The method is based on the measurement of absorbance of the zinc(II)-PAN chelate solubilized with a non-ionic surfactant, Triton X-100, no extraction procedure is required in the proposed method, yielding a pink colored complex at pH 9.5 with absorption maximum at 553 nm. The SIA parameters that affect the signal response have been optimized in order to get the better sensitivity and minimum reagent consumption. A linear relationship between the relative peak height and concentration was obtained in the concentration range of 0.1-1.0 μg ml-1. The limit of detection (LOD, defined as 3σ) and limit of quantification (LOQ, defined as 10σ) were 0.02 and 0.06 μg ml-1, respectively. The sample throughput about 40 samples/h was obtained. The repeatability were 1.32 and 1.24% (n = 10) for 0.1 and 0.5 μg ml-1, respectively. The proposed method was successfully applied to the assay of zinc(II) in three samples of multivitamin tablets. The results were found to be in good agreement with those obtained by flame atomic absorption spectrophotometric method and with the claimed values by the manufactures. The t-test showed no significant difference at 95% confidence level. © 2006.